PERLINDUNGAN HUKUM TERHADAP KARYAWAN YANG BEKERJA SHIFT MALAM (STUDI PADA PT INDOMARCO PRISMATAMA) - Faisal, Muhamad; Arman, Zuhdi (SCIENTIA JOURNAL, 2020)
HumankResources (HR) is thehmost importantyasset in akcompany. Employeeshcan be a goodhpotential if managedhproperly andhcorrectly, butkemployees canjalso become a burden if thekcompany cannot managekthem well. Along with the increase in the business world, especially companieshengaged in retail in the city of Batam, which has become negative in the eyes of the public related to work safety, workplace accidents, occupational diseases, This study is entitled "Legal protection for employees who work the night shift (study at PT INDOMARCO PRISMATAMA)". This paper aims to find out in depth about the implementation of legal protection and the factors that influence the implementation of legal protection for employees who work at night at PT INDOMARCO PRISMATAMA. This type of research is empirical juridical research, which examines problems or facts that occur in the field based on laws and regulations. Data collection techniques using observation, interviews and documentation. In this case the owner or entrepreneur of PT INDOMARCO PRISMATAMA has been quite effective in implementing the provisions stipulated in the Law of the Republic of IndonesiakNumber 13 ofo2003 but one thing that cannot be implemented is the lack of security for employees who work night shifts. The reality on the ground is that most of the workers themselves object to the lack of safety guarantees when working at night. Author's suggestion for PT INDOMARACO PRISMATAMA to pay moremattention toksecurity andhsafety for employees,kbecause every human being has the right to obtain a safe and peaceful life Keyword: Legal protection; legal certainty; labor safety;